1995
DOI: 10.1182/blood.v86.7.2590.bloodjournal8672590
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow stromal cells induce myeloid and lymphoid development of the sorted hematopoietic stem cells in vitro

Abstract: Regulation of development of hematopoietic stem cells was examined by culturing Lin- c-Kit+ Sca1+ stem cells sorted from bone marrow (BM) cells by fluorescence-activated cell sorting on a layer of TBR59, a BM stromal cell line established from simian virus 40 T-antigen gene transgenic mice. The sorted stem cells did not show self-renewal, but two waves (at 7 and 13 days) of a cobblestone formation were induced by the stromal cell layer. The cobblestones were formed by finite cell division (eight divisions on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Similar to our findings in canine long-term marrow culture, Okuyama et al have described a biphasic development of myeloid (first wave) and lymphoid (second wave) cells in an in Vitro model in which mouse purified stem cells were cultured over a stromal cell line (35). Appearance of myeloid and lymphoid cells has been also reported in the SCID-hu system (36).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to our findings in canine long-term marrow culture, Okuyama et al have described a biphasic development of myeloid (first wave) and lymphoid (second wave) cells in an in Vitro model in which mouse purified stem cells were cultured over a stromal cell line (35). Appearance of myeloid and lymphoid cells has been also reported in the SCID-hu system (36).…”
Section: Discussionsupporting
confidence: 89%
“…It is likely Tissue Antigens 1998: 51: 141-155 that in myelopoiesis, the hematopoietic cells must adhere to the stromal cells through VLA-4-VCAM-1 interaction, but their continuous interaction is not required for further proliferation and differentiation of the hematopoietic cells. However, their continuous interaction may be required for lymphopoiesis (35).…”
Section: Discussionmentioning
confidence: 99%
“…Yolk sac cells were inoculated into 0.8% methylcellulose and cultured in the presence of erythropoietin (2 U/ml) and stem cell factor (SCF; 50 ng/ml) (Okuyama et al, 1995), and the numbers of colonies (colonyforming unit-erythroid, CFU-E) formed were counted.…”
Section: Colony Assaymentioning
confidence: 99%
“…Examination of the supporting ability of two typical stromal cell lines showed that TBR59 can induce cobblestone formations committed to myelopoiesis and lymphopoiesis of the sorted stem cells (Okuyama et al 1995a). Another cell line, TBR31-1 was shown to specifically induce B-lymphopoiesis from the same sorted stem cell population.…”
Section: Bone Marrow Stromal Cell Lines That Support Growth and Diffementioning
confidence: 99%